The Philippines stingless bee propolis promotes hair growth through activation of Wnt/β-catenin signaling pathway - Tang, Yulan; Wang, Chen; Desamero, Mark Joseph M.; Mun, Keong Kok; Chambers, James Kenn; Uchida, Kazuyuki; Kominami, Yuri; Ushio, Hideki; Cervancia, Cleofas; Estacio, Maria Amelita; Kyuwa, Shigeru; Kakuta, Shigeru (J-Stage, 2022)
Although hair loss is not a horrible disease, it sometimes reduces the patients' quality of life (QOL) and increases their mental stress. Currently, there is no effective treatment for hair loss. It is known that honeybee propolis has various biological activities, including stimulating the proliferation of hair matrix keratinocytes. However, little is known with the hair promoting activity of stingless bee propolis. Hence, this study investigates the hair growth-promoting activity of Philippines stingless bee propolis extract and the underlying a molecular mechanism of promoting hair growth. For the evaluation of hair growth stimulating activity, 99.5% ethanolic extract of Philippines stingless bee propolis is examined using the simple shaving model in C57BL/6N mice. Melaninization of dorsal skin and histological analysis of hair follicles (HFs) revealed that propolis promotes hair growth by stimulating HFs development. The expression of mRNA (Wnt3a, Ctnnb1/β-catenin, Lef1, and Bmp2) and protein (WNT3A and β-catenin) of selected Wnt/β-catenin associated genes explains Philippines stingless bee propolis promoting HFs development by activating Wnt/β-catenin signaling pathway. These results suggest that the treatment of propolis strongly promotes hair growth by stimulating the development of HFs via activation of Wnt/β-catenin signaling pathway. This further indicates the potential of Philippines stingless bee propolis as a novel promising agricultural product for hair growth.